2016
DOI: 10.1016/j.gene.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Expressed miRNAs target feather related mRNAs involved in cell signaling, cell adhesion and structure during chicken epidermal development

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression at the post-transcriptional level. Previous studies have shown that miRNA regulation contributes to a diverse set of processes including cellular differentiation and morphogenesis which leads to the creation of different cell types in multicellular organisms and is thus key to animal development. Feathers are one of the most distinctive features of extant birds and are important for multiple functions including flight, thermal regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 96 publications
(143 reference statements)
1
13
0
Order By: Relevance
“…vectorbase. org/), as reported elsewhere [27]. The predicted binding sites were additionally corroborated with RNAhybrid (http:// bibiserv.…”
Section: Bioinformaticssupporting
confidence: 73%
“…vectorbase. org/), as reported elsewhere [27]. The predicted binding sites were additionally corroborated with RNAhybrid (http:// bibiserv.…”
Section: Bioinformaticssupporting
confidence: 73%
“…Feather-keratin is involved in the elongation of barbule cells in feathers where small proteins (i.e., β-keratins) rich in glycine, serine, and proline have evolved in birds to reinforce the mechanical resistance of feathers [ 57 ]. Interestingly, retinoic acid signaling appears to be important for the timing and expression of FKR and other β-keratins in the avian epidermis [ 58 ]. In the present study, we found differential expression of several enzymes involved in retinol metabolism (see Additional file 5 ), retinol transport and over-representation of RXR signaling in liver of rd / rd chick embryos at e15 (see Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…2018 ) and miRNAs that target the cell signaling, cell adhesion, and cell structure genes required in feather morphogenesis ( Zhang et al. 2013 ; Bao et al. 2016 ).…”
Section: Diversity Of Feather Morphotypementioning
confidence: 99%